A techno-economic analysis of a solar PV and DC battery storage system for a community energy sharing. (1st April 2022) - Gul, Eid; Baldinelli, Giorgio; Bartocci, Pietro; Bianchi, Francesco; Piergiovanni, Domenighini; Cotana, Franco; Wang, Jinwen
Abstract: Energy harvesting from renewable sources can play a vital role to decarbonize the environment, limit global warming and mitigate the growing energy demand. The objective of this work consists of decarbonizing a University Campus and neighboring communities by producing electricity from solar photovoltaic systems integrated with an energy storage system and local grid station. A new mathematical model is developed to maximize the system power generation and balance the load demand. The simulation and optimization software System Advisor Model (SAM) is used to develop and test model results. The software is used to analyze and optimize the solar energy generation, the energy demand, and the economic performance: capital cost, overall investment, net present value, and the Levelized Cost of Energy of the project. A novel approach decentralized load centers is adopted to share power with adjacent communities. At the aim of improving the system flexibility, reliability, and climate resilience, the established model is grid-connected. The CO2 emissions reduction is also determined to evaluate the environmental impact of the interventions. Highlights: PV-battery based energy system model for community energy sharing. Sustainable and socio-economic feasible energy mix solution for urban and sub-urban areas. Economic and environmental analysis of Grid connected PV-battery system.